A prospective comparative study of surgical release of carpal tunnel syndrome with and without flexor tenosynovectomy - Ranjeet, Niraj; Thapa, Pabin; Sapkota, Krishna; Onta, Pratyenta Raj; Thapa, Upendra Jung; Wahegoankar, Krishna (Asian Journal of Medical Sciences, 2022)
Background: Carpal tunnel syndrome (CTS) is a common condition causing hand pain and numbness. The rationale of tenosynovectomy is to remove the flexor tenosynovium that is contributing to increased volume within the carpal canal, thus removal of this tenosynovium should give more space for the median nerve and there by relief from symptoms. Aims and Objectives: The main objective of our study was to assess the role of routine flexor tenosynovectomy in the treatment of CTS. Materials and Methods: Eighty-six hands with CTS were randomized into two groups, either to carpal tunnel release with or without flexor tenosynovectomy. All patients were requested to fill up the self-administered questionnaire for the assessment of symptom severity and functional status, examined for 2-point discrimination, grip and pinch strength, scar tenderness and patient satisfaction score preoperatively, 2 weeks, 1 month, and 6 months follow-up. Results: After the surgical release, both groups improved significantly with respect to symptom severity and functional status, 2-point discrimination, grip and pinch strength, scar tenderness and patient satisfaction score but there was no significant difference between the two groups. There were two cases of post-operative wound infection and one case of mild reflex sympathetic dystrophy. Conclusion: We conclude that routine flexor tenosynovectomy during surgical release of carpal tunnel in patients with CTS does not provide any added benefit nor does it increase any morbidity.